2006
DOI: 10.1159/000095457
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in the Allergenicity of Japanese Cedar Pollen Allergen by Treatment with Positive and Negative Cluster Ions

Abstract: Background: Japanese cedar pollinosis is a severe allergic disease in Japan. The most effective means of decreasing allergic inflammation reactions is still avoidance of the aeroallergen. Recently, a novel air purification system using positively and negatively charged cluster ions was developed to create comfortable living environments. We aimed to assess the ability of existing technology to lower allergenicity of Japanese cedar pollen. Methods: A Japanese cedar pollen extract was nebulized from the top of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 71 publications
3
26
0
Order By: Relevance
“…Additionally, studies investigating the effect of reactive species (excluding O 3 ) from a corona discharge on dust mite and cat allergens have shown that these allergens, which differ structurally for one another, can be destroyed by exposure to the corona discharge products (36,37). Similar results were obtained with Japanese cedar pollen (38).…”
Section: Discussionsupporting
confidence: 52%
“…Additionally, studies investigating the effect of reactive species (excluding O 3 ) from a corona discharge on dust mite and cat allergens have shown that these allergens, which differ structurally for one another, can be destroyed by exposure to the corona discharge products (36,37). Similar results were obtained with Japanese cedar pollen (38).…”
Section: Discussionsupporting
confidence: 52%
“…For the experimental chamber analysis, we used a cylindrical experimental apparatus (14.5 cm in diameter, 52.5 cm high) as previously described [9]. The cylindrical apparatus was filled with PCIs generated from a PCI-generating device (a second-generation Plasma Cluster™ device, Sharp Corp., Osaka, Japan) for 15 min, followed by 8 mL of atomized 200 ng/mL HDM extract solution.…”
Section: Methodsmentioning
confidence: 99%
“…The cylindrical apparatus was filled with PCIs generated from a PCI-generating device (a second-generation Plasma Cluster™ device, Sharp Corp., Osaka, Japan) for 15 min, followed by 8 mL of atomized 200 ng/mL HDM extract solution. The PCI-treated HDM solution was then collected in a petri dish at the bottom of the apparatus [9,10]. A 1-m 3 acrylic box equipped with a PCI-generating device (a second-generation Plasma Cluster™ device, Sharp Corp.) and a stirring fan were used for the evaluation of the effects of PCIs under a simulated indoor environmental condition (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations